Bioeconomic efficiency of mineral fertilization in sorghum crop (Research, Society and Development, 2022)
Climate change posed major agricultural challenges regarding adaptation, fertilizer use and tolerant crops. Thus, the objective of this review was to investigate the assumptions of mineral fertilization in sorghum and to present a bioeconomic efficiency of this culture when managed with the use of mineral fertilization. To achieve satisfactory results, one of the premises that must be followed is a nutritional requirement of mineral fertilization according to the nutritional requirement of the culture. In sorghum, this requirement varies according to the productivity of the crop in each growing situation. A number of soil nutrients follows a linear pattern according to the increase in productivity, indicating that the more the crop is conditioned to high levels of productivity, the greater the withdrawal of nutrients from the system. The most extracted from the culture are phosphorus, nutrients, potentially calcium and magnesium, and their order of obtaining and accumulating macronutrients: K > N > Ca > Fe > Zn > Mn > N > Ca > Mn > Mn Cu. There are still few researches that describe the best cost-benefit of the use of nutrients in order to enhance the forage supply. Therefore, it is recommended to carry out more eco-pronomic research designed for the efficiency of mineral fertilization in the production of sorghum in production systems, and consequently, promoting the development of systems. socioeconomic status of the regions involved in sorghum cultivation.